How to approach consumers' nonmonetary evaluation of electricity supply security? The case of Germany from a multidisciplinary perspective. (October 2016) - Becker, Sophia; Schober, Dominik; Wassermann, Sandra
Abstract: Consumers' preferences regarding the security of supply (SoS) of electricity are generally assessed through economic estimates of the value of lost load . However, this monodisciplinary approach typically builds on homo oeconomicus assumptions and neglects consumers' non monetary evaluations of SoS. This can result in short-sighted regulation, especially in the context of a transition like Germany's Energiewende . This paper provides a consumer-centered perspective on SoS employing psychological and sociological research on energy. German consumers' strong involvement in the Energiewende and their strong commitment to it make them a fascinating case. To determine the practical implications, we explore under what circumstances altered levels of SoS could be acceptable to consumers. Highlights: Provide a consumer-centered perspective on security of supply in the Energiewende . Transfer results from psychological and sociological studies to supply security. Consumers' nonmonetary evaluations should be considered in energy regulation. Explore under what circumstances short outages could be acceptable to consumers.